![Para x=-1, o valor de (2x)^{2x} -x^{-2} =<br />
Para x=-1, o valor de (2x)^{2x} -x^{-2} =<br />](https://tex.z-dn.net/?f=Para%C2%A0+x%3D-1%2C+o+%C2%A0valor+%C2%A0de++%282x%29%5E%7B2x%7D++-x%5E%7B-2%7D+%3D%3Cbr+%2F%3E%0A)
a)-1
b)![\frac{-3}{4} <br />
\frac{-3}{4} <br />](https://tex.z-dn.net/?f=+%5Cfrac%7B-3%7D%7B4%7D+%3Cbr+%2F%3E%0A)
c)![- \frac{1}{4} - \frac{1}{4}](https://tex.z-dn.net/?f=-+%5Cfrac%7B1%7D%7B4%7D+)
d)
Soluções para a tarefa
Respondido por
4
Oi Iris,
Segue o passo a passo
Segue o passo a passo
Respondido por
1
Olá Iris
(2x)^2x - x^-2
(-2)^-2 - (-1)^-2
1/4 - 1 = 1/4 - 4/4 = -3/4 (B)
(2x)^2x - x^-2
(-2)^-2 - (-1)^-2
1/4 - 1 = 1/4 - 4/4 = -3/4 (B)
Perguntas interessantes
Matemática,
1 ano atrás
Direito,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás